2019
DOI: 10.1101/842260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonthermal plasma treatment of polymers modulates biological fouling but can cause material embrittlement

Abstract: Plasma-based treatment is a prevalent strategy to alter biological response and enhance biomaterial coating quality at the surfaces of biomedical devices and implants, especially polymeric materials. Plasma, an ionized gas, is often thought to have negligible effects on the bulk properties of prosthetic substrates given that it alters the surface chemistry on only the outermost few nanometers of material. However, no studies to date have systematically explored the effects of plasma exposure on both the surfac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
(36 reference statements)
3
3
0
Order By: Relevance
“…The coating for the 0.08 pCD surface was found to have delaminated during a rinse step, so no data is shown for that sample. Plasma treatments were observed to reduce protein adsorption onto PP surfaces, in agreement with previous findings 83 , again possibly a result of increasing wettability.…”
Section: Effects Of Hdi-crosslinking On Pcd Resistance To Non-specifisupporting
confidence: 90%
See 2 more Smart Citations
“…The coating for the 0.08 pCD surface was found to have delaminated during a rinse step, so no data is shown for that sample. Plasma treatments were observed to reduce protein adsorption onto PP surfaces, in agreement with previous findings 83 , again possibly a result of increasing wettability.…”
Section: Effects Of Hdi-crosslinking On Pcd Resistance To Non-specifisupporting
confidence: 90%
“…Cell adhesion was equally low for untreated PP as for most pCD polymers (p > 0.293). Plasma treatment of PP increased cell adhesion (p = 0.01), consistent with prior findings 83 . Likewise, cell adhesion for TCPS (commercially plasma-treated PS) was higher than that for untreated PS (p < 0.003).…”
Section: Effects Of Hdi-crosslinking On Pcd Resistance To Mammalian Csupporting
confidence: 90%
See 1 more Smart Citation
“…We herein used both in silico and in vitro measurements to predict and confirm the relative affinity of the selected drugs for β-CD or the base polymer without inclusion complex formation, dextran (Figures 1 and 2). Previous studies have demonstrated using cyclodextrin monomers polymerized into larger macrostructures such as coatings, disks, and particles in order to delay drug release by achieving a high concentration of affinity-binding sites [27,30,31,37,44,45]. The release results herein show differences in the loading efficiencies (Figure 3), release rates ( Figure 4), and cumulative amounts of drug release ( Figure 5) which may inform the future use and design of local drug delivery depots.…”
Section: Discussionmentioning
confidence: 84%
“…The lack of a need for hazardous chemical treatments is an advantageous aspect of substrate plasma activation, especially for coatings to be applied to polymeric biomedical implants, such as PP sutures and hernia meshes. Appropriate selection of plasma treatment parameters can ensure minimal impact on the bulk mechanical properties of such load-bearing substrates 6 . Apart from biomedical purposes, this research has important commercial applications as well.…”
Section: Discussionmentioning
confidence: 99%